PATOLOGI SOSIAL DALAM PERSPEKTIF AL-QUR’AN (Kajian Tentang Makna Al-Su' Dan Fahisyah Sebagai Konsep Patologi Sosial) - Mahmud, Hamidullah (UIN Mataram, 2022)
Religion can be likened to a straight bridge to human life. Whether a person or a community of people is bad depends on how humans interpret religion as their way of life, and only Islam is the only religion that can be such a straight bridge. Seeing the current reality where damage occurs in every inch of life to become a disease of society that is difficult to cure which in social science is called social pathology. To restore a harmonious social life, reviving religious values as one of the social controls is a necessity. As a social control, religion is very effective in answering the solution of social problems that occur today, a dry life of divine values. Long before social problems or social pathologies were widely discussed by sociologists, the Qur'an as a source of life guidelines had informed about the existence of symptoms of this social pathology even though it did not use popular language in the study of social sciences. For example, the words al-S?' and f?hisyah contained in the Quran have meanings that are in harmony with the meaning of social pathology, such as murder, adultery or cheating, homosexuals and lesbians, and so on. This paper will only discuss one of the perspectives of the concept of social pathology in the Qur'an, namely the terms al-S?' and f?hisyah with the scope they contain.